Epstein-Barr Virus-Positive Lymphoma-Associated Hemophagocytic Syndrome: A Retrospective, Single-Center Study of 51 Patients - Zhao, Ailin; Yang, Jinrong; Li, Meng; Li, Linfeng; Gan, Xinai; Wang, Jie; Li, He; Shen, Kai; Yang, Yunfan; Niu, Ting (Frontiers in Immunology, 2022)
Purpose To investigate clinical characteristics, management, and prognosis of Epstein-Barr virus (EBV)-positive lymphoma-associated hemophagocytic syndrome (LAHS) patients in real-world practice. Methods This was a retrospective, single-center cohort study. EBV-positive LAHS patients diagnosed from January 2010 to December 2021 in our center were enrolled. Clinical characteristics, treatment, overall response rate (ORR), and overall survival (OS) were investigated. Univariate and multivariate analysis of potential factors were conducted. Results Of the 51 patients, 44 were T/NK cell lymphoma; five were B cell lymphoma; two were Hodgkin lymphoma. EBV-positive T/NK cell LAHS patients were significantly younger and showed lower fibrinogen levels and C-reactive protein levels than EBV-positive B cell LAHS patients (P=0.033, P=0.000, and P=0.004, respectively). Combined treatment of anti-hemophagocytic lymphohistiocytosis (HLH) and anti-lymphoma treatment was conducted in 24 patients; anti-HLH treatment was conducted in 18 patients; anti-lymphoma treatment was conducted in three patients; glucocorticoid treatment was conducted in one patient. ORR was 47.8%, and the median OS was 61 (95% confidence interval 47.9-74.1) days for overall patients. Patients who received anti-HLH treatment and turned to anti-lymphoma treatment early displayed higher ORR and OS than those of anti-HLH patients (P=0.103, and P=0.003, respectively). Elevated alanine aminotransferase level was the independent risk factor of EBV-positive LAHS prognosis. Conclusions Prognosis of EBV-positive LAHS patients was poor. Anti-lymphoma treatment should be initiated as soon as HLH was rapidly controlled.